Hot corrosion behaviour of Gd2O3 doped LaMgAl11O19 thermal barrier coating exposed to molten V2O5 at 900 °C. Issue 13 (1st July 2021) - Cao, Shengjun; Sun, Junbin; Chen, Ting; Wang, Juan; Chen, Mansheng; Hui, Yu; Wang, Jinshuang; Li, Wenyi; Lu, Weihong
Abstract: This study investigates the hot corrosion behaviours of La1- x Gd x MgAl11 O19 ( x = 0, 0.2, 0.4, 0.6, 0.8) bulk ceramics and ceramic coatings. The hot corrosion resistance of the ceramic coating was inferior to that of the bulk ceramic, owing to the formation of an amorphous phase during the plasma spraying process. The smaller size of Gd 3+ in comparison with La 3+ facilitated the ready combination of Gd 3+ with V O 4 3 − . LaVO4 was obtained as the corrosion product in the LaMgAl11 O19 (LMA) sample. Upon doping the LMA with Gd2 O3, the LaVO4 was almost entirely replaced by GdVO4 . Therefore, the sacrificial action of GdMgAl11 O19 protected the LMA from hot corrosion, while also providing a new method for modifying the corrosion resistance of molten slag.